Plant extracellular vesicles: A promising bionic medicine platform for disease treatment and drug delivery - Jichun Yang; Yuhan Wang; Yunqian Fu; Sitong Wang; Yao Luo; Xin Cui; Chenyu Sun; Jianing Ji; Jiaxi Mo; Yang Wang; Yilin Liu; Xinghong Hu; et al. (Interdisciplinary Medicine)
Abstract Plant extracellular vesicles (PEVs) are nanoscale vesicles secreted by plant cells with intact membrane architecture, which encapsulate a diverse array of biomolecules, including lipids, proteins and RNA. They are integral to both intra‐cellular communication within plants and inter‐species signaling. Recently, some PEVs have been regarded as competitive candidates for disease therapy due to their beneficial components and distinctive hollow biomembrane structure. However, the broader applications of PEVs are currently impeded by several challenges of complicated extraction processes, compositional heterogeneity, the lack of reliable biomarkers and unclear therapy mechanisms. A detailed comprehension of their preparation techniques and biological functions is essential for leveraging their potential in clinical medicine. This article first presented a synthesis of the current methodologies for PEV isolation, purification and characterization. Then, it revealed the therapeutic implications of PEVs as medicines in some common diseases based on their bioactive molecules inside, such as cancer, inflammation, and metabolic disorders. We especially explored the emerging role of PEVs with low immunogenicity and the power for biological barriers crossing as drug delivery systems, underscoring their potential for further industry and clinical applications. At last, the bottleneck problems and a vision of PEVs for disease therapy were also presented to evoke more insightful deliberation. This review aims to provide directions for the development of PEV‐derived innovative drugs.